2013
DOI: 10.3233/ip-130305
|View full text |Cite
|
Sign up to set email alerts
|

U.S. public safety networks: Architectural patterns and performance

Abstract: Through this paper we advance insights regarding common patterns among information and communication technology (ICT) architectures (ICTA) found in United States' public safety networks (PSNs). A PSN is an inter-organizational collaboration enabled by ICT to support information sharing and interoperability needs of police and associated public safety organizations. Substantial evidence makes clear the information systems designed and used by PSNs are typically expensiveand complex, support multiple public agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The Police are not obliged to use ELC, which is why the criminal file is not sent via this system in all cases. In addition, the Police have the option to send structured data (i.e., extracted from the IT system) or scanned documents that have been transferred to PDF via ELC…In order to connect EliAs (i.e., the Electronically-Integrated Assistant system) to the other systems in the criminal justice chain, such as ELC and PAD (the system with which the Police work internally), all these systems have been expanded with a specific link that allowed the systems to communicate with each other and documents could be read from one system to the other (Ibid, p. 105/106) Once again, this finding sheds a new light on existing IT governance research (e.g., Benfeldt et al, 2020;Buchwald, Urbach & Ahlemann, 2014;Constantinides & Barrett, 2015;Eaton et al, 2018;Fedorowicz et al, 2018;Sawyer et al, 2013;etc. ) because it emphasizes the role of technology as a governance structure that goes above and beyond other regulative forces enshrined within social structures.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The Police are not obliged to use ELC, which is why the criminal file is not sent via this system in all cases. In addition, the Police have the option to send structured data (i.e., extracted from the IT system) or scanned documents that have been transferred to PDF via ELC…In order to connect EliAs (i.e., the Electronically-Integrated Assistant system) to the other systems in the criminal justice chain, such as ELC and PAD (the system with which the Police work internally), all these systems have been expanded with a specific link that allowed the systems to communicate with each other and documents could be read from one system to the other (Ibid, p. 105/106) Once again, this finding sheds a new light on existing IT governance research (e.g., Benfeldt et al, 2020;Buchwald, Urbach & Ahlemann, 2014;Constantinides & Barrett, 2015;Eaton et al, 2018;Fedorowicz et al, 2018;Sawyer et al, 2013;etc. ) because it emphasizes the role of technology as a governance structure that goes above and beyond other regulative forces enshrined within social structures.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, Pardo et al (2012) have devised a model of multi-dimensional capabilities for information sharing within e-Government that includes both social (e.g., strategic, governance, and operational capabilities) and technological dimensions (e.g., business architectures, security standards, and technology compatibility). By the same token, Sawyer et al, (2013) have developed a framework that embodies the strategic, operational, and technological dimensions that play a central role in understanding the function of ITs in digital government and identified two core configurations of successful IT-enabled information sharing revolving around data management issues (Courts) and integration and interoperability issues (Police). Lastly, and related to Sawyer's et al (2013) findings, Fedorowicz et al (2018) have stressed the importance of network-level governance competencies to manage stakeholders and information infrastructures in the context of PSNs.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we include two distinguishing aspects of PSN that may help to differentiate among the political forces that affect PSN formation: type and legal arrangement. In prior research (Sawyer et al, 2013), we have shown PSN with common goals and shared information infrastructure fall into two broad and distinct types (as police-oriented or as court-oriented). We include categorization of these types in the analysis to assess if the particular orientation of the PSN plays a special role in its governance.…”
Section: Research Questionmentioning
confidence: 97%